Chile's Millennium Science Initiative : Building Human Capital for the Global Knowledge Economy - Holm-Nielsen, Lauritz (World Bank, Washington, DC, 2012)
Chile's scientific community garners well-deserved respect in the region and worldwide. The country has made significant and fruitful efforts to move towards a leadership position in research among industrializing countries. While progress has been substantial it has not yet matched the country's aspirations and much remains to be done. Although, there are no observed specific inequities within Chile's advanced research system, the country's education system has room for improvement. In higher education, while gender equity has been attained, there is still an uneven concentration of enrollment in the top income quintile, 65 percent, while the two lowest quintiles merely reached 25.6 percent in 2000. In terms of postgraduates, Chile produces less than 100 Ph.D.s per year and would need to be producing on the order of 3,000 per annum to reach a level comparable to the knowledge-based OECD economies. Similarly, Chile has one scientist for each thousand economically active inhabitants, while the developed world has an average of five scientists per thousand.